Use of clay sorptive materials in the synthesis of polymer materials - Kryklyvyi, Rostyslav; Sakalova, Halyna; Petrushka, Kateryna; Luchyt, Liubov (Видавництво Львівської політехніки, 2022)
The paper suggests the solution to the urgent problem of increasing the level of environmental safety of industrial wastewater treatment from heavy metal using natural and modified bentonite.The use of spent bentonite in the processes of filling polymers is investigated. The aim of the research was to study the influence of fillers on the crosslinking course and functional properties of vulcanized elastomeric mixtures. Test research compositions included chloroprene rubber and chlorosulfonated polyethylene. Nanofillers were used as a strengthening substance. Montmorillonite and spent montmorillonite saturated with copper ions were used as nanofiller.
Keywords: rubber; filling; montmorillonite; heavy metal ions